Megahertz scan rates enabled by optical sampling by repetition-rate tuning - D. Bajek (Nature Portfolio, 2021)
Abstract We demonstrate, for the first time, optical sampling by repetition-rate tuning (OSBERT) at record megahertz scan rates. A low-cost, tunable and extremely compact 2-section passively mode-locked laser diode (MLLD) is used as the pulsed laser source, whose repetition rate can be modulated electronically through biasing of the saturable absorber section. The pulsed output is split into two arms comparable to an imbalanced Michelson interferometer, where one arm is significantly longer than the other (a passive delay line, or PDL). The resulting electronic detuning of the repetition rate gives rise to a temporal delay between pulse pairs at a detector; the basis for time-resolved spectroscopy. Through impedance-matching, we developed a new system whereby a sinusoidal electrical bias could be applied to the absorber section of the MLLD via a signal generator, whose frequency could be instantly increased from sub-hertz through to megahertz modulation frequencies, corresponding to a ground-breaking megahertz optical sampling scan rate, which was experimentally demonstrated by the real-time acquisition of a cross-correlation trace of two ultrashort optical pulses within just 1 microsecond of real time. This represents scan rates which are three orders of magnitude greater than the recorded demonstrations of OSBERT to date, and paves the way for highly competitive scan rates across the field of time-resolved spectroscopy and applications therein which range from pump probe spectroscopy to metrology.